A theoretical outline of the importance of cross-cultural and pragmatic awareness in the business scenario - Soprana, Victor Marques (BELT - Brazilian English Language Teaching Journal, 2017)
English has become crucial for professional success within the globalized world, and indispensable for communicating with people from other countries. It has become a Lingua Franca and, therefore, has been used to speak among people with different mother tongues who share English as a second language. In light of this multicultural process, this paper aims to provide the reader with a theoretical outline about the relevance of cross-cultural and pragmatic knowledge. Such aspects need to be specially considered when developing an English course for business students as there has been a growing need for professionals to be competent users of English within the business context. Due to this specific context, we have favored an approach – English for Specific Purposes – that targets specific aspects of the language. Our focal point is to validate the need of raising both pragmatic and cross-cultural awareness when teaching business professionals as they will probably have communicative scenarios where such capabilities would be remarkably advantageous.